Ductal Carcinoma Arising in a Squamous Epithelial Inclusion Cyst within an Axillary Lymph Node: A Challenging Nodal Metastasis - Kaitlyn J. Nielson; Ruifeng Guo; Malvika H. Solanki; Charles D. Sturgis (Hindawi Limited, 2023)
Introduction. Assessment of axillary lymph nodes in breast carcinoma is an important part of staging to guide appropriate clinical management. Lymph node inclusions of different types, including nevoid, squamous, and glandular, are rare but have been reported in multiple different anatomic locations including the axilla. These can result in diagnostic challenges and pose risks of misdiagnoses. Rarely, malignancies may arise intrinsic to otherwise incidental benign nodal inclusions. Case Presentation. We report a case of ductal carcinoma diagnosed within a squamous epithelial inclusion cyst within an axillary lymph node in a patient with pure ductal carcinoma in situ (DCIS) of the ipsilateral right breast. To our knowledge, this is the fifth report in the literature of breast carcinoma confirmed within an axillary inclusion in a patient with pure DCIS. Evaluation of the primary DCIS and lymph node inclusions, by routine and immunohistochemical stains, was performed for assessment. Discussion. The presence of lymph node inclusions can pose a challenge in assessment of benignity and malignancy, on frozen and permanent histologic sections. Pathologists should carefully evaluate lymph node inclusions to ensure that intrinsic malignancies are not missed within rare otherwise benign appearing incidental epithelial rests.